Digital Montage Based Visual Simulation to Evaluate Spatial Identity in the Idjen Street Heritage Corridor, Malang, Indonesia - herry santosa; Rohadatul Aisy; Dwi Septi Permatasari; Kiara Angela Pranoto (Jurnal Koridor, 2026)
Historic urban corridors possess diverse visual characteristics and distinctive features that cannot be captured through conventional photographic survey techniques or through 3D modeling per building. This study aims to develop a digital simulation workflow framework based on montage to reconstruct and evaluate the spatial characteristics of the historic corridor of Jalan Idjen in Malang, Indonesia, which is one of the important historical landscape heritages that is starting to undergo rapid commercial transformation. This research method integrates sequential photo mapping, panoramic photo montage, 3D modeling with low-polygon techniques, and the implementation of immersive rendering to represent the integration of visual sequences that create spatial continuity, façade rhythm, and mass proportions. The novelty of this research is to translate visual perception at the scale of urban corridors into a qualitative evaluation through immersive modeling as a research gap in the digital visual study of historic landscapes. The results of this study reveal that qualitative evaluations of visual quality, spatial legibility, and aesthetic coherence indicate that the uniformity of building height and setbacks and the presence of vegetation strengthen the identity of the historic corridor, while the presence of signage, color inconsistencies, and fragmentation of building masses create visual continuity disruptions. Furthermore, the development of this research workflow framework has proven to be efficient and easily replicable for diagnosing other corridor segments, in supporting the sensitivity of conservation policies and controlling the growth rate of the visual and spatial layout of historic urban corridors.